2003
DOI: 10.1046/j.1365-3059.2003.00862.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of partial resistance in potato cultivars exposed to aggressive strains ofPhytophthora infestans

Abstract: Potato cultivars were evaluated for their resistance responses to aggressive strains of Phytophthora infestans in field and laboratory experiments. Analysis of variance revealed differential cultivar-by-isolate interactions for both foliar and tuber blight resistance. Differential responses occur as revealed by specific susceptibilities of cultivars to certain pathogen genotypes and changing rank order. In general, severity of late blight epidemics as observed in the haulms did not correlate well with foliar b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 36 publications
1
51
1
Order By: Relevance
“…A similar trend was observed for accessions UCT-32Ci and UCT-33cab. Wide variation in response to this disease in potato have been reported by various authors (Micheletto et al, 2000;Flier et al, 2003;Jenkins & Jones, 2003;Barquero et al, 2005a;Lucca et al, 2008;Andreu et al, 2009;Mendoza, 2010). Barquero et al (2005b) reported the existence of important differences between genotypes resulting from crosses with different wild species.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…A similar trend was observed for accessions UCT-32Ci and UCT-33cab. Wide variation in response to this disease in potato have been reported by various authors (Micheletto et al, 2000;Flier et al, 2003;Jenkins & Jones, 2003;Barquero et al, 2005a;Lucca et al, 2008;Andreu et al, 2009;Mendoza, 2010). Barquero et al (2005b) reported the existence of important differences between genotypes resulting from crosses with different wild species.…”
Section: Discussionmentioning
confidence: 77%
“…Initially the search concentrated on specific resistance (Flier et al, 2003;Forbes et al, 2005). This type of resistance is characterized by a hypersensitive response in the form of small necrotic lesions, and is called race-specific, monogenic, qualitative, or complete resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the late blight resistance test, detached leaf assays (DLAs) were performed as described by Vleeshouwers et al (1999). The P. infestans isolates IPO82001 (race structure: 1, 2, 3 ,4, 5, 6, 7, 10, 11) and IPO655-2A (race structure 1,2,3,4,5,6,7,8,10,11) (Flier et al 2003) were from the collection of PRI, isolate "Marknesse" (race structure: 1, 2, 3, 4, 6, 7, 10, 11) was from a diseased potato collected in 2005 near the Dutch village Marknesse.…”
Section: Segregating Populations and Resistance Assaysmentioning
confidence: 99%
“…The field tests for late blight resistance consisted of three randomised blocks with two plants per plot. Plants were inoculated approximately 8 weeks after emergence by spray application of a spore suspension of race 1.2.3.4.5.6.7.10.11 of P. infestans (IPO82001; Flier et al, 2003). Percentages of late blight-affected leaf tissue were assessed over a period of 6 weeks after inoculation at weekly intervals in the year 2000 and twice a week in 2001.…”
Section: Phenotypic Evaluationsmentioning
confidence: 99%